Nutrient accumulation curves in fruits and nutrient export by seeds and hulls harvesting of physic nut (Jatropha curcas L.) - Silva de Lima, Rosiane de Lourdes; Sofiatti, Valdinei; Vieira de Azevedo, Carlos Alberto; Cazetta, Jairo Osvaldo; Carvalho Júnior, Genelicio Souza [UNESP]; Castro Arriel, Nair Helena (Univ Estadual Londrina, 2014)
There is little information on the nutritional management of physic nut (Jatropha curcas L.). This study aimed to measure the nutrients accumulation during the growth of fruits in physic nut and the nutrients export from the area due to seed harvest and hull removal. Fruits were harvested at different times (11, 19, 27, 35, 43, 51, and 59 days after anthesis), in a completely randomized design with four replications. Nutrient content was measured in the whole fruit and in the hull and seed separately. Nutrients accumulate in the fruit during its growth. Nitrogen is the nutrient accumulated in the greatest amount, followed by potassium, calcium, phosphorus, magnesium, and sulfur. For the micronutrients, their content decreased in order of: zinc, manganese, copper, and iron. There was a high demand for Ca, Mg, Cu, Zn, and Mn in the early fruit development. The physic nut fruit requires significant amounts of micronutrients for normal fruit growth. Potassium is the nutrient exported in the greatest amount through a hull.
Keywords: Jatropha curcas; Export by harvest; Mineral nutrition